'Wanna race?': Primary student preference for competitive or non-competitive singing games. Issue 2 (11th January 2016) - Roberts, J. Christopher
Abstract : This study compared primary student preference for competitive and non-competitive singing games. Students in three intact classes of second graders ( n = 65) and three classes of fourth graders ( n = 67) at one school in the USA served as subjects. After playing a pair of games, one competitive and one non-competitive, over the course of five classes, students anonymously named their preferred game and reported reasons for their preference. Results indicated that the students significantly preferred the competitive game, regardless of grade level or gender. The most common reason students provided for their preference was the higher level of kinaesthetic activity.